Efficacy and Safety of Cinnamon Stomachic Mixture for Patients with Functional Dyspepsia - Jindarat, Sunanta; Muangnoi, Chaweewan; Changsiriporn, Dalicha; Platong, Anuchit; Thanamontra, Bangon; Chiewchanwit, Duangrat; Vongvanvatana, Viparat; Rongrungsri, Noppawan; Krittasilp, Kumrai; Kaewkong, Nutteera; Kantawan, Sairung; Virasombat, Nilnetr; et al. (Siriraj Medical Journal, 2006)
Health care personnel at a community hospital have used cinnamon stomachic mixture for treatment of patients with functional dyspepsia for many years and they claimed that cinnamon stomachic mixture was effective without any supportive evidence. Objective: To determine the efficacy, safety, patients’ compliance and satisfaction with the treatment of cinnamon stomachic mixture. Methods: This was a randomized controlled study in 318 adults with functional dyspepsia presenting to 6 community hospitals. The patients were randomized to receive 105 mg of simethicone three times a day or 30 ml of cinnamon stomachic mixture three times a day for 7 to 14 days. The patients were evaluated for improvement of symptoms, compliance to medication and patients’ satisfaction with the treatment. The data were analysed by descriptive statistics, chi-square statistics, student t test, analysis of variance and non-parametric tests where appropriate. Results: One hundred and fifty patients received simethicone and 168 patients received cinnamon stomachic mixture. The baseline characteristics of the patients in both groups were not significantly different. The patients’ compliance to simethicone and cinnamon stomachic mixture was 82% and 89.3% respectively (p=0.09). The severity of the symptoms after treatment and the response rates were not significantly different between both groups. Side effects were observed in 9.3% and 9.5% in the simethicone group and the cinnamon stomachic mixture group respectively. Most of the patients in both groups were satisfied with the treatments they received. The cost of a 14-day course of cinnamon stomachic mixture was 36 baht compared with 84 baht for that of simethicone. Conclusion: Cinnamon stomachic mixture is effective and safe for the treatment of the patients with functional dyspepsia similar to simethicone.